PENGARUH TEMPERATUR DAN UKURAN PARTIKEL BIOMASSA TERHADAP BIO-OIL HASIL PIROLISIS AMPAS TEBU / BAGGASE - Ariany Zulkania (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
The bio-oil production from baggase using pyrolysis process was investigated in this study. A fixed bed reactor was utilized to investigate the effect of pyrolysis temperature and biomass particle size on the yield of bio-oil, tar, biochar and gas and properties of bio-oil. The pyrolysis temperature was ranging from 450 to 550oC, while variations of particle size were -20+30 Mesh and -30+40 Mesh. The operation conditions of the pyrolysis were 15 minutes of resident time, 25oC/minute of heating ramp and 0.5 L/min of N2 flowrate. Optimum conditions obtained for the maximum bio-oil yield (28.11 %wt) were 550oC and -30+40 Mesh of particle size. However, pyrolysis for -20+30 Mesh of biomass particle size had optimum temperature on 500oC which had 27.89%wt of bio-oil yield. On the other hand, all bio-oils were characterized in detail by determining their density, viscosity, pH, acetic acid content and heating value. Bio-oils produced have the following properties: density of 1.0667-1.0867 gr/ml, viscosity of 1.3034-1.7821 cP, pH of 2.3835-2.7865, acetic acid content of 0.4320-0.5600 mg/ml bio-oil, dan heating value of 9.3168-10.8173 MJ/kg. The highest heating value is contented by bio-oil produced with 550oC of temperature pyrolysis and -30+40 Mesh of biomass particle size.